Religious Discourse & the Reproduction of Injustice Against Marginalized Workers - Fiqi Restu Subekti; Noni Kensiwi (PT Polstac Repositori Riset, 2026)
This study investigates how religious discourse is employed to reproduce injustices against marginalized workers within contemporary workplace settings. Aimed at identifying discursive forms, analyzing the factors that facilitate the reproduction of injustice, and exploring its consequences, the study adopts a literature-review approach that traces news coverage, public opinion, and social-media discourse as primary data sources. The findings reveal three principal forms through which injustice is reproduced: (1) the ideologization of moral values that reframes structural problems as personal failings; (2) the sacralization of hierarchical structures that grants moral legitimacy to managerial authority; and (3) the instrumentalization of religious symbols and rituals as mechanisms of social control. Factors reinforcing these processes include conservative religious interpretations, entrenched structural power relations, the psychological internalization of religious values, and cultural norms promoting compliance. The implications comprise an erosion of workers’ critical consciousness, the reinforcement of socio-economic inequality, increased psychological and spiritual burdens, and a weakening of labor solidarity. The study concludes that religious discourse can operate as a tool for conserving the status quo rather than as a catalyst for social justice.